2021
DOI: 10.12659/msm.933880
|View full text |Cite
|
Sign up to set email alerts
|

Blood Pressure Rhythm and Blood Pressure Variability as Risk Factors for White Matter Lesions: A Cross-Sectional Study

Abstract: Background White matter lesions are common in the elderly. The aim of this study was to explore the correlation between blood pressure rhythm and blood pressure variability with white matter lesions. Material/Methods A total of 144 subjects aged 40 to 80 years underwent MRI scanning to assess the degree of white matter lesions using the Fazekas scale. The regional cerebral blood flow was detected by brain perfusion imaging, and an ambulatory blood pressure monitor was u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…In hypertensive patients, blood pressure variability and impaired blood pressure rhythm resulting in reduced localized blood flow to the white matter of the brain may be an essential cause of LA. Both acute and chronic elevated blood pressure leads to systemic adaptive vascular remodeling, causing damage to multiple end organs, including the brain 23 - 24 . Recently, relevant studies have shown that in adults with hypertension, patients with systolic blood pressure less than 120 mmHg (intensive hypotension) had a smaller increase in the volume of cerebral white matter lesions and a greater decrease in total brain volume compared to patients with systolic blood pressure less than 140 mmHg 25 .…”
Section: Discussionmentioning
confidence: 99%
“…In hypertensive patients, blood pressure variability and impaired blood pressure rhythm resulting in reduced localized blood flow to the white matter of the brain may be an essential cause of LA. Both acute and chronic elevated blood pressure leads to systemic adaptive vascular remodeling, causing damage to multiple end organs, including the brain 23 - 24 . Recently, relevant studies have shown that in adults with hypertension, patients with systolic blood pressure less than 120 mmHg (intensive hypotension) had a smaller increase in the volume of cerebral white matter lesions and a greater decrease in total brain volume compared to patients with systolic blood pressure less than 140 mmHg 25 .…”
Section: Discussionmentioning
confidence: 99%
“…We found that both SBPV and DBPV can promote WMH development. In addition, by studying the relationship between Blood pressure CV and WMH, Zhang et al found that systolic blood pressure CV (OR = 1.589,95 % CI 1.273–1.983) and diastolic blood pressure CV (OR = 1.363,95 % CI 1.150–1.616) were significantly correlated with Fazekas score (P < 0.05) [ 43 ]. Moreover, some studies have further pointed out that both short-term SBPV and long-term SBPV cause varying degrees of damage to WMH [ 32 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Blood pressure rhythm (BPR) and blood pressure variability (BPV) increase the risk of WMLs, which have recently been linked to hypertension and aging. Reducing regional cerebral blood flow was associated with increased BPV and rhythm abnormalities in individuals with WMLs [ 9 ], indicating that disruptions in BPR or increased BPV may impede WML advancement through this mechanism.…”
Section: Reviewmentioning
confidence: 99%